Positive electrode active material for lithium secondary battery and method for producing same

JP7608013B2Active Publication Date: 2025-01-06LG CHEM LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023558237
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-10-15
Filing Date
2022-10-14
Publication Date
2025-01-06
Estimated Expiration
2042-10-14

AI Technical Summary

Benefits of technology

【0012】 本発明の製造方法によって正極活物質を製造した時に、過焼成を行うことで、単粒子形態の正極活物質を製造し、且つ正極活物質のコーティング層に位置した一次粒子の粒径と成分を制御することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007608013000004
    Figure 0007608013000004
  • Figure 0007608013000005
    Figure 0007608013000005
  • Figure 0007608013000006
    Figure 0007608013000006
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material for a lithium secondary battery and a method for producing the positive electrode active material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0137697 filed on October 15, 2021, and all contents disclosed in the documents of said Korean patent application are incorporated as part of this specification.

[0002] The present invention relates to a positive electrode active material for a lithium secondary battery and a method for producing the positive electrode active material. [Background technology]

[0003] With the technological development and increasing demand for mobile devices, the demand for secondary batteries as an energy source is rapidly increasing. Among such secondary batteries, lithium secondary batteries, which have high energy density and voltage, long cycle life, and low self-discharge rate, have been commercialized and are widely used.

[0004] Lithium transition metal composite oxides are used as the positive electrode active material of lithium secondary batteries, and among them, lithium cobalt composite metal oxides such as LiCoO2, which have high working voltage and excellent capacity characteristics, are mainly used. However, LiCoO2 has very poor thermal characteristics due to the instability of the crystal structure caused by delithiation. In addition, the LiCoO2 is expensive, so there is a limit to its mass use as a power source in fields such as electric vehicles.

[0005] As a material to be used in place of LiCoO2, lithium manganese composite metal oxides (LiMnO2 or LiMn2O4, etc.), lithium iron phosphate compounds (LiFePO4, etc.), lithium nickel composite metal oxides (LiNiO2, etc.), etc. have been developed. Among them, research and development of lithium nickel composite metal oxides, which have a high reversible capacity of about 200 mAh / g and can easily realize large-capacity batteries, has been actively carried out. However, LiNiO2 has inferior thermal stability compared to LiCoO2, and if an internal short circuit occurs due to external pressure in a charged state, the positive electrode active material itself is decomposed, causing the battery to explode and catch fire. Therefore, as a method of maintaining the excellent reversible capacity of LiNiO2 and improving its low thermal stability, lithium transition metal oxides in which part of Ni is replaced with Co, Mn, or Al have been developed.

[0006] However, in the case of the lithium transition metal oxide, when the content of nickel is increased in order to improve the capacity characteristic, the thermal stability is further decreased, and the nickel in the lithium transition metal oxide becomes Ni 2+ As a result, there is a problem that a large amount of lithium by-products such as LiOH or Li2CO3 are generated on the surface. When a lithium transition metal oxide having a high content of lithium by-products on its surface is used as a positive electrode active material, it reacts with the electrolyte injected into the lithium secondary battery, causing gas generation and swelling of the battery, which may result in a decrease in battery life, stability, and battery resistance characteristics.

[0007] Therefore, there is a need for the development of a positive electrode active material that exhibits high capacity characteristics and improves particle strength and structural stability, thereby enabling the production of secondary batteries with improved resistance characteristics and cycle performance. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Korean Patent Publication No. 10-2014-0093529 Summary of the Invention [Problem to be solved by the invention]

[0009] An object of the present invention is to provide a positive electrode active material having improved surface properties, suppressing the formation of a rock-salt structure, and improving resistance properties and cycle performance. [Means for solving the problem]

[0010] In order to solve the above problems, the present invention provides a lithium transition metal oxide containing 60 mol % or more of nickel relative to the total moles of transition metals other than lithium, and a coating layer containing a metal oxide located on the surface of the lithium transition metal oxide, the lithium transition metal oxide having an average particle diameter (D 50 The metal oxide is a single particle including primary particles having an average particle diameter (D 50 The positive electrode active material is a primary particle having a particle size of 0.5 μm or less, and contains one or more metal elements selected from the group consisting of Ni, Co, Mn, Al, B, Ti, Ta, W, and Nb.

[0011] The present invention also provides a method for producing a positive electrode active material, comprising the steps of: (S1) preparing a transition metal hydroxide containing 60 mol % or more of nickel based on the total moles of the transition metals; (S2) mixing the transition metal hydroxide with a lithium raw material and firing the mixture at a temperature of 800 to 890°C to produce a single-particle lithium transition metal oxide; (S3) heat-treating the lithium transition metal oxide at a temperature 30 to 50°C higher than the firing temperature; and (S4) mixing the heat-treated lithium transition metal oxide with a coating raw material containing one or more metal elements selected from the group consisting of Ni, Co, Mn, Al, B, Ti, Ta, W, and Nb, and heat-treating the mixture. Effect of the Invention

[0012] When the positive electrode active material is manufactured by the manufacturing method of the present invention, the positive electrode active material in the form of a single particle can be manufactured by over-firing, and the particle size and composition of the primary particles located in the coating layer of the positive electrode active material can be controlled.

[0013] The positive electrode active material according to the present invention has excellent stability in a battery, and therefore can improve battery performance such as capacity retention rate and life characteristics. [Brief description of the drawings]

[0014] [Figure 1] 1 is a SEM image showing the positive electrode active material of Example 1. [Diagram 2] 1 is a SEM image showing the positive electrode active material of Comparative Example 1. [Diagram 3] 1 is a SEM image showing the positive electrode active material of Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The present invention will now be described in further detail in order to facilitate understanding of the present invention.

[0016] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of ​​the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.

[0017] <Cathode active material> The positive electrode active material of the present invention includes a lithium transition metal oxide containing 60 mol % or more of nickel relative to the total moles of transition metals other than lithium, and a coating layer containing a metal oxide located on the surface of the lithium transition metal oxide, the lithium transition metal oxide having an average particle size (D 50 The metal oxide is a single particle including primary particles having an average particle diameter (D 50) is a primary particle having a diameter of 0.5 μm or less, and is characterized in that it contains one or more metal elements selected from the group consisting of Ni, Co, Mn, Al, B, Ti, Ta, W and Nb.

[0018] The lithium transition metal oxide is a high-nickel (High-Ni) NCM-based lithium transition metal oxide containing nickel (Ni), cobalt (Co) and manganese (Mn), and having a nickel (Ni) content of 60 mol% or more based on the total moles of transition metals other than lithium (Li). The nickel content may be 70 mol% or more, or 80 mol% or more based on the total moles of transition metals other than lithium (Li). As described above, by having a nickel (Ni) content of 60 mol% or more based on the total moles of transition metals other than lithium (Li), it is possible to realize high capacity and ensure excellent stability.

[0019] However, Ni relative to the nickel content 2+ If the mole fraction is too high, the cation mixing can increase and local electrochemically unreactive rock salt structures can form, which can impede charge and discharge, thereby reducing discharge capacity, and once formed, the rock salt structures can continue to diffuse within the particle, further degrading performance.

[0020] Therefore, in the present invention, as described below, the diffusion of the rock salt structure is suppressed by disposing primary particles having a small particle size in a coating layer located on the surface of the lithium transition metal oxide. Also, by using a metal oxide containing one or more metal elements selected from the group consisting of Ni, Co, Mn, Al, B, Ti, Ta, W, and Nb as the primary particles located in the coating layer, the nickel content of the surface is reduced compared to the lithium transition metal oxide, effectively preventing the formation of the rock salt structure.

[0021] The lithium transition metal oxide may be represented by the following Formula 1:

[0022] [Chemical formula 1] Li 1+a Ni x Co y Mn z M 1 w O2

[0023] In the chemical formula 1, M 1 is at least one selected from the group consisting of Al, Mg, V, Ti, and Zr, 0 ≦ a ≦ 0.5, 0.6 ≦ x < 1, 0 < y ≦ 0.4, 0 < z ≦ 0.4, 0 < w ≦ 0.04, and x + y + z + w = 1.

[0024] In the chemical formula 1, 1 + a represents the molar ratio of lithium in the lithium transition metal oxide represented by the chemical formula 1, and 0 ≦ a ≦ 0.5, 0 ≦ a ≦ 0.20, preferably 0 ≦ a ≦ 0.15.

[0025] x represents the molar ratio of nickel among the metal components other than lithium in the lithium transition metal oxide represented by the chemical formula 1, and 0.6 ≦ x < 1.0, preferably 0.8 ≦ x < 1.0.

[0026] y represents the molar ratio of cobalt among the metal components other than lithium in the lithium transition metal oxide represented by the chemical formula 1, 0 < y ≦ 0.4, and considering the significance of the improvement effect of capacity characteristics by including Co, preferably 0 < y ≦ 0.2.

[0027] z represents the molar ratio of manganese among the metal components other than lithium in the lithium transition metal oxide represented by the chemical formula 1, 0 < z ≦ 0.4, preferably 0 < z ≦ 0.2.

[0028] The M 1 is an element substituted at the transition metal site in the lithium transition metal oxide represented by the chemical formula 1 and can contain at least one or more selected from the group consisting of Al, Mg, V, Ti, and Zr.

[0029] In the lithium transition metal oxide represented by Chemical Formula 1, w represents the molar ratio of the doping element M among the metal components other than lithium, and 0 < w ≤ 0.04, preferably 0 ≤ w ≤ 0.02.

[0030] The lithium transition metal oxide is a single particle containing primary particles with an average particle diameter (D 50 ) of 0.7 to 3 μm.

[0031] The term "single particle" is used to distinguish from the positive electrode active material particles in the form of secondary particles formed by aggregation of dozens to hundreds of primary particles that have been conventionally and generally used, and is a concept including aggregate particles of 10 or fewer primary particles. The "secondary particle" means an aggregate in which primary particles are aggregated by physical or chemical bonding between the primary particles without an intentional aggregation or granulation process for the primary particles, that is, a secondary structure.

[0032] The "primary particle" means the smallest particle unit distinguished as one mass when observing the cross-section of the positive electrode active material through a scanning electron microscope (SEM), and can be composed of one crystal grain or can be composed of a plurality of crystal grains. In the present invention, the average particle diameter of the primary particles can be measured by a method of measuring each particle diameter distinguished by the cross-section SEM data of the positive electrode active material particles and then obtaining the arithmetic mean value thereof.

[0033] The "average particle diameter (D 50 )" can be defined as the particle diameter based on the 50% standard of the volume cumulative particle diameter distribution and can be measured using the laser diffraction method. Specifically, the average particle diameter (D 50 ) is obtained by dispersing the target particles in a dispersion medium, introducing them into a commercially available laser diffraction particle size measuring device (for example, Microtrac MT 3000), irradiating with ultrasonic waves of about 28 kHz at an output of 60 W, and then calculating the average particle diameter (D 50 ) based on the 50% standard of the particle volume cumulative distribution by particle diameter in the measuring device.

[0034] The average particle size of the primary particles constituting the single particle (D 50 ) is 0.7 to 3 μm. More preferably, the average particle size of the primary particles (D 50 ) can be 1 to 3 μm, most preferably 1.5 to 2.5 μm.

[0035] The lithium transition metal oxide contained in the positive electrode active material of the present invention has an average particle size (D 50 ), it is possible to suppress the formation of cracks due to charge / discharge cycles and prevent electrolyte from penetrating between the cracks, thereby improving the life characteristics of the battery. At the same time, the lithium transition metal oxide coating layer is provided with primary particles smaller in size than the primary particles constituting the lithium transition metal oxide, thereby minimizing the deterioration of performance due to the diffusion of the rock salt structure.

[0036] The average particle diameter of the single particles (D 50 ) is 1 to 10 μm. Preferably, it can be 2 to 7 μm, 3 to 6 μm, or 3.5 to 5 μm. The lithium transition metal oxide contained in the positive electrode active material of the present invention is formed of single particles, so that the average particle size (D 50 Even if the particle size is small, that is, 1 to 10 μm, the particle strength can be excellent.

[0037] The single particle may be composed of 2 to 30 primary particles, specifically, 3 to 25 or 5 to 20 primary particles. When the number of primary particles constituting a single particle is within the above range, the battery output and resistance characteristics can be improved compared to a single particle composed of only one large primary particle.

[0038] The positive electrode active material of the present invention includes a coating layer that is located on the surface of the lithium transition metal oxide and includes a metal oxide. The coating layer is distinguished from the single particle form of the lithium transition metal oxide and can refer to a region where the metal oxide is located on the surface.

[0039] Here, the metal oxide has an average particle size (D 50 ) is a primary particle having a diameter of 0.5 μm or less, and contains one or more metal elements selected from the group consisting of Ni, Co, Mn, Al, B, Ti, Ta, W and Nb.

[0040] The metal oxide may be derived from a reaction between a lithium by-product on the surface of the lithium transition metal oxide and a coating raw material containing one or more metal elements selected from the group consisting of Ni, Co, Mn, Al, B, Ti, Ta, W, and Nb. For example, the metal oxide may be a lithium-metal oxide formed by reacting a lithium by-product with a metal oxide containing one or more metal elements selected from the group consisting of Ni, Co, Mn, Al, B, Ti, Ta, W, and Nb.

[0041] In the present invention, the coating layer in the positive electrode active material is located on the surface of the lithium transition metal oxide and includes a metal oxide, and the metal oxide is a primary particle having an average particle size (D 50 ) can be 0.5 μm or less, preferably 0.1 to 0.3 μm.

[0042] The metal oxide has an average particle size (D 50 ), in the present invention, the particle size of the primary particles is small, which can suppress rapid diffusion of the rock salt structure and minimize the increase in thickness of the rock salt structure and the resulting deterioration of performance.

[0043] The fact that the metal oxide in the coating layer is a primary particle is not limited by the position or form of the primary particle in the coating layer. Specifically, as long as the metal oxide is a primary particle having the above average particle size, the primary particles may be located on the surface of the lithium transition metal oxide in a non-aggregated state, some of the primary particles may be aggregated to form aggregates, and some of the primary particles may be present in a non-aggregated state. The present invention also includes all primary particles that form aggregates. When some or all of the primary particles are aggregated, the relative proportion or position of the aggregates of the primary particles and the non-aggregated primary particles is not limited.

[0044] In the present invention, the coating layer containing a metal oxide and located on the surface of the lithium transition metal oxide may have a thickness of 0.02 to 2.4 μm, specifically, 0.1 to 1.2 μm, or 0.2 to 0.5 μm. When the coating layer has a thickness within the above range, the diffusion of rock salt structures on the surface of the lithium transition metal oxide can be effectively suppressed, and side reactions caused by an increase in the surface area of ​​the coating layer due to a small particle size of the primary particles can be minimized.

[0045] In the present invention, the volume ratio of the lithium transition metal oxide and the coating layer may be 50:50 to 95:5, specifically 70:30 to 90:10. Within this range, the above-mentioned single particle characteristics can be maintained, and the prevention of diffusion of the rock salt structure due to the gradient of the primary particle size between the lithium transition metal oxide and the coating layer can be effectively realized.

[0046] The coating layer may be formed on the entire or partial surface of the lithium transition metal oxide. When the coating layer is formed partially on the surface of the lithium transition metal oxide, it may be formed on 20% or more and less than 100% of the total surface area of ​​the lithium transition metal oxide. When the area of ​​the coating layer is 20% or more as described above, the formation of the coating layer can sufficiently improve the life characteristics of the battery and the packing density.

[0047] <Method of manufacturing positive electrode active material> The method for producing a positive electrode active material of the present invention includes the steps of: (S1) preparing a transition metal hydroxide containing 60 mol % or more of nickel based on the total moles of transition metals; (S2) mixing the transition metal hydroxide with a lithium raw material and firing the mixture at a temperature of 800 to 890°C to produce a single-particle lithium transition metal oxide; (S3) heat-treating the lithium transition metal oxide at a temperature 30 to 50°C higher than the firing temperature; and (S4) mixing the heat-treated lithium transition metal oxide with a coating raw material containing one or more metal elements selected from the group consisting of Ni, Co, Mn, Al, B, Ti, Ta, W, and Nb, and heat-treating the mixture.

[0048] In step (S1), a transition metal hydroxide containing 60 mol % or more of nickel based on the total number of moles of the transition metals is prepared.

[0049] The transition metal hydroxide may be a commercially available positive electrode active material precursor, or may be prepared by a method for preparing a positive electrode active material precursor that is well known in the art.

[0050] For example, the transition metal hydroxide may be prepared by adding an ammonium cation-containing complex former and a basic compound to a transition metal solution containing a nickel-containing raw material, a cobalt-containing raw material, and a manganese-containing raw material, and then subjecting the mixture to a coprecipitation reaction.

[0051] In step (S2), the transition metal hydroxide and a lithium source material are mixed and sintered at a temperature of 800 to 890° C. to produce a single particle lithium transition metal oxide.

[0052] That is, the positive electrode active material is produced in the form of a single particle by performing the firing at a temperature of 800 to 890°C. When the firing temperature is within the above range, the single particle having high crystallinity can be provided, and the particle size of the single particle can be effectively controlled. The firing temperature can be 800 to 890°C, and preferably 800 to 850°C.

[0053] The lithium source material may be, but is not limited to, a lithium-containing carbonate (e.g., lithium carbonate, etc.), a hydrate (e.g., lithium hydroxide I hydrate (LiOH·H2O), etc.), a hydroxide (e.g., lithium hydroxide, etc.), a nitrate (e.g., lithium nitrate (LiNO3), etc.), a chloride (e.g., lithium chloride (LiCl), etc.), etc.

[0054] The calcination may be performed in an oxygen or air atmosphere for 5 to 25 hours. When the calcination is performed in the atmosphere, the local oxygen partial pressure is increased, which improves the crystallinity of the positive electrode active material and makes it easier to control the surface.

[0055] In addition, during the preparation of the lithium transition metal oxide, a doping element M may be selectively added as necessary to improve the structural stability of the lithium transition metal oxide. 1 (wherein, the M 1 The method may further include doping with at least one element selected from the group consisting of Al, Mg, V, Ti and Zr. For example, the lithium transition metal oxide may further include doping with a doping element M 1 When doped with the doping element M 1 is a doping element M during the coprecipitation reaction for producing the positive electrode active material precursor. 1 The doping can be performed by adding a raw material, or the doping element M can be added during the sintering of the positive electrode active material precursor and the lithium raw material. 1 By inputting raw materials, M 1 Doped lithium transition metal oxides can be prepared.

[0056] In step (S3), the lithium transition metal oxide is heat-treated at a temperature 30 to 50° C. higher than the calcination temperature. Specifically, the lithium transition metal oxide can be heated to a temperature 30 to 50° C. or 30 to 40° C., for example, 30° C. higher than the calcination temperature, and then the temperature can be lowered.

[0057] The heat treatment sufficiently generates lithium by-products such as LiOH or Li2CO3 on the surface of the lithium transition metal oxide. The lithium by-products react with the coating raw material on the surface of the lithium transition metal oxide to form an average particle size (D 50 ) can form a metal oxide in the form of primary particles having a size of 0.5 μm or less to form a coating layer.

[0058] If the heat treatment process is omitted, the lithium by-products are not sufficiently present on the surface of the lithium transition metal compound. In this case, the formation of new primary particles induced by the reaction between the coating raw material and the lithium by-products cannot be sufficiently performed, and a uniform coating layer is generally formed in which the coating raw material covers the lithium transition metal oxide. As a result, it is difficult to achieve the effect of inhibiting the rock salt structure diffusion using small primary particles located in the coating layer.

[0059] In step (S4), the heat-treated lithium transition metal oxide is mixed with a coating raw material containing one or more metal elements selected from the group consisting of Ni, Co, Mn, Al, B, Ti, Ta, W and Nb, and then heat-treated.

[0060] The heat treatment induces a reaction between the lithium by-product and the coating raw material on the surface of the lithium transition metal oxide, forming a dot shape, specifically an average particle size (D 50 ) of 0.5 μm or less can be stably formed. As a result, the positive electrode active material of the present invention exhibits excellent particle strength due to its high structural stability.

[0061] The coating raw material can be any material that contains at least one metal element selected from the group consisting of Ni, Co, Mn, Al, B, Ti, Ta, W, and Nb and can form a metal oxide by reacting with lithium by-products. For example, when the coating raw material contains Co as a metal element, the coating raw material can be, but is not limited to, Co3O4, Co(OH)2, Co2O3, Co3(PO4)2, CoF3, CoOOH, Co(OCOCH3)2·4H2O, Co(NO3)·6H2O, Co3O4, Co(SO2)2·7H2O, and CoC2O4.

[0062] In step (S4), the heat treatment may be performed at a temperature of 600 to 700° C. in an oxygen or air atmosphere. When sintering is performed in the atmosphere, the local oxygen partial pressure is increased, improving the crystallinity of the positive electrode active material and making it easier to control the surface.

[0063] In addition, the manufacturing method of the present invention may further include a step of washing the cathode active material synthesized by the above method with water.

[0064] For example, the positive electrode active material is mixed with a washing solution (preferably distilled water) and washed with water, whereby lithium by-products present as impurities on the surface of the positive electrode active material can be effectively removed.

[0065] Furthermore, the manufacturing method of the present invention may further include a step of forming a coating layer after the water washing step. Preferably, the coating layer may contain B, but is not limited thereto.

[0066] For example, the coating element is dispersed in a solvent to prepare a composition for forming a coating layer, and the coating layer is then surface-treated on the positive electrode active material using a typical slurry coating method such as application, immersion, or spraying, followed by heat treatment, whereby the coating layer can be formed on the surface of the positive electrode active material.

[0067] The solvent in which the coating elements can be dispersed to form the coating layer may be one or more mixtures selected from the group consisting of water, alcohols having 1 to 8 carbon atoms, dimethylsulfoxide (DMSO), n-methylpyrrolidone, acetone, and combinations thereof. The solvent may be included in an amount that can exhibit suitable applicability and can be easily removed during subsequent heat treatment.

[0068] Next, the heat treatment for forming the coating layer may be performed in a temperature range capable of removing the solvent contained in the composition, specifically, 100 to 500° C., preferably 200 to 400° C. If the heat treatment temperature is less than 100° C., there is a risk of side reactions occurring due to the residual solvent and thus deteriorating the battery characteristics, and if the heat treatment temperature exceeds 500° C., there is a risk of side reactions occurring due to high heat.

[0069] <Positive electrode> The present invention also provides a positive electrode for a lithium secondary battery, which contains the positive electrode active material produced by the above-mentioned method.

[0070] Specifically, the positive electrode includes a positive electrode current collector and a positive electrode active material layer located on at least one surface of the positive electrode current collector and including the above-mentioned positive electrode active material.

[0071] The positive electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface treated with carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode current collector can usually have a thickness of 3 to 500 μm, and fine irregularities can be formed on the surface of the current collector to increase the adhesive force of the positive electrode active material. For example, it can be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0072] The positive electrode active material layer may contain a conductive material and a binder in addition to the positive electrode active material.

[0073] In this case, the positive electrode active material may be included in an amount of 80 to 99 wt %, more specifically, 85 to 98 wt %, based on the total weight of the positive electrode active material layer. When included in the above content range, excellent capacity characteristics can be exhibited.

[0074] In this case, the conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it does not cause a chemical change in the battery to be constructed and has electronic conductivity. Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and one or more of these can be used alone or in combination. The conductive material can be contained in an amount of 1 to 30% by weight based on the total weight of the positive electrode active material layer.

[0075] The binder serves to improve the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, and various copolymers thereof, and one or more of these may be used alone or in combination. The binder may be included in an amount of 1 to 30% by weight based on the total weight of the positive electrode active material layer.

[0076] The positive electrode may be manufactured by a typical method for manufacturing a positive electrode, except for using the positive electrode active material. Specifically, the positive electrode may be manufactured by dissolving or dispersing the positive electrode active material and, optionally, a binder and a conductive material in a solvent to prepare a positive electrode mixture, which is then coated on a positive electrode current collector, followed by drying and rolling. In this case, the types and contents of the positive electrode active material, binder, and conductive material are as described above.

[0077] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and may be used alone or in combination of two or more of these. The amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, conductive material, and binder, and to provide a viscosity that allows excellent thickness uniformity during subsequent coating for the manufacture of a positive electrode, taking into consideration the coating thickness of the slurry and the manufacturing yield.

[0078] Alternatively, the positive electrode can be produced by casting the positive electrode mixture on a separate support, peeling it off from the support, and laminating the resulting film on a positive electrode current collector.

[0079] Lithium secondary battery In addition, the present invention can provide an electrochemical device including the positive electrode. The electrochemical device can be, for example, a battery or a capacitor, and more specifically, a lithium secondary battery.

[0080] Specifically, the lithium secondary battery includes a positive electrode, a negative electrode facing the positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte. Since the positive electrode is as described above, a detailed description thereof will be omitted, and only the remaining components will be described in detail below.

[0081] Also, the lithium secondary battery may optionally further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.

[0082] In the lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0083] The negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may have a thickness of usually 3 μm to 500 μm, and like the positive electrode current collector, the surface of the current collector may be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0084] The negative electrode active material layer includes a negative electrode active material, and optionally a binder and a conductive material.

[0085] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO β (0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, and lithium vanadium oxide; or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites or Sn-C composites, and any one or a mixture of two or more of these may be used. In addition, a metallic lithium thin film may be used as the negative electrode active material. In addition, the carbonaceous material may be either low crystalline carbon or high crystalline carbon. Representative examples of low crystalline carbon include soft carbon and hard carbon, and representative examples of high crystalline carbon include amorphous, plate-like, flake-like, spherical or fibrous natural or artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, meso-carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes.

[0086] The negative electrode active material may be contained in an amount of 80 to 99% by weight based on the total weight of the negative electrode active material layer.

[0087] The binder is a component that facilitates bonding between the conductive material, the active material, and the current collector, and is usually added in an amount of 0.1 to 10 parts by weight per 100 parts by weight of the total weight of the negative electrode active material layer. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile-butadiene rubber, fluororubber, and various copolymers thereof.

[0088] The conductive material is a component for further improving the conductivity of the negative electrode active material, and may be added in an amount of 10% by weight or less, specifically 5% by weight or less, based on the total weight of the negative electrode active material layer. Such a conductive material is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and examples of such conductive materials include graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.

[0089] For example, the negative electrode active material layer can be produced by applying a negative electrode mixture, which is prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent, onto a negative electrode current collector and drying the applied material; alternatively, the negative electrode mixture can be cast onto another support, and then peeled off from the support to obtain a film, which can be laminated onto the negative electrode current collector.

[0090] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator that is generally used as a separator in a lithium secondary battery can be used without any particular limitation. In particular, a separator that has low resistance to ion movement of the electrolyte and has excellent humidification ability of the electrolyte solution is preferable. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof can be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high-melting point glass fiber, a polyethylene terephthalate fiber, etc., can be used. In addition, a coated separator containing a ceramic component or a polymeric material can be used to ensure heat resistance or mechanical strength, and can be selectively used as a single layer or a multilayer structure.

[0091] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the production of lithium secondary batteries, but are not limited to these.

[0092] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0093] The organic solvent can be used without any particular limitation as long as it serves as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent can be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone; an ether solvent such as dibutyl ether or tetrahydrofuran; a ketone solvent such as cyclohexanone; an aromatic hydrocarbon solvent such as benzene or fluorobenzene; dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Carbonate-based solvents such as ethylene carbonate (PC); alcohol-based solvents such as ethyl alcohol and isopropyl alcohol; nitriles such as R-CN (R is a straight-chain, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or sulfolanes may be used. Among them, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant that can improve the charge / discharge performance of a battery and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred. In this case, the cyclic carbonate and the linear carbonate are mixed in a volume ratio of about 1:1 to about 1:9, so that the electrolyte can exhibit excellent performance.

[0094] The lithium salt can be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The concentration of the lithium salt is preferably within the range of 0.1 to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, so that it can exhibit excellent electrolyte performance and lithium ions can move effectively.

[0095] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for improving the life characteristics of the battery, suppressing the decrease in the capacity of the battery, improving the discharge capacity of the battery, etc. In this case, the additives may be contained in an amount of 0.1 to 5 parts by weight based on 100 parts by weight of the total weight of the electrolyte.

[0096] As described above, the lithium secondary battery including the positive electrode active material according to the present invention stably exhibits excellent discharge capacity, output characteristics and life characteristics, and is therefore useful in portable devices such as mobile phones, notebook computers and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).

[0097] Therefore, according to another embodiment of the present invention, there is provided a battery module including the lithium secondary battery as a unit cell, and a battery pack including the same.

[0098] The battery module or battery pack may be used as a power source for one or more medium- to large-sized devices, such as a power tool; an electric vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV); or a power storage system.

[0099] The external shape of the lithium secondary battery of the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, or the like.

[0100] The lithium secondary battery according to the present invention can be used not only as a battery cell used as a power source for a small device, but also preferably as a unit battery in a medium- to large-sized battery module including a large number of battery cells.

[0101] Working Example The present invention will be described in more detail with reference to the following examples. However, the following examples are for illustrating the present invention, and the scope of the present invention is not limited to these examples.

[0102] Example 1 Positive electrode active material precursor Ni 0.85 Co 0.05 Mn 0.10 The lithium source LiOH was mixed with (OH)2, and the mixed powder was placed in an alumina crucible for heat treatment. It was then fired at 825°C in an oxygen atmosphere for 20 hours to produce lithium transition metal oxide.

[0103] Then, the lithium transition metal oxide was crushed and heat-treated in an oxygen atmosphere at 855° C., and then mixed with Co3O4 and heat-treated in an oxygen atmosphere at 650° C. to prepare a positive electrode active material.

[0104] Comparative Example 1 A positive electrode active material was produced in the same manner as in Example 1, except that the step of heat-treating in an oxygen atmosphere at 855° C. and the step of mixing with Co3O4 and heat-treating in an oxygen atmosphere at 650° C. were not performed.

[0105] Comparative Example 2 A positive electrode active material was produced in the same manner as in Example 1, except that the step of heat treatment at 855° C. in an oxygen atmosphere was not carried out.

[0106] Experimental example 1: Confirmation of the surface of the positive electrode active material The surfaces of the positive electrode active materials of Example 1 and Comparative Examples 1 and 2 were confirmed and are shown in FIGS.

[0107] As shown in FIGS. 1 to 3, in Example 1, the inside where the lithium transition metal oxide was located was in the form of single particles, and a coating layer was formed in which the primary particle size became smaller toward the surface.

[0108] On the other hand, in Comparative Example 1, no coating layer made of primary particles was formed on the surface of the lithium transition metal oxide, and only a small number of primary particles that could not be formed as single particles were observed to remain.

[0109] In addition, in the case of Comparative Example 2, a coating layer formation step of mixing with Co3O4 and heat-treating was performed, but it was confirmed that only a uniform and smooth coating layer was located on the surface without any gradient in the primary particle size, unlike Example 1. This is because the step of generating lithium by-products on the surface of the lithium transition metal oxide through heat treatment was omitted in Comparative Example 2.

[0110] Experimental Example 2: Average particle size of positive electrode active material The average particle size of the primary particles constituting the lithium transition metal oxide (single particle) and the average particle size of the primary particles which are the metal oxide contained in the coating layer were measured for the positive electrode active material particles prepared in Example 1 and Comparative Examples 1 and 2. SEM photographs were used to measure the average particle size.

[0111] [Table 1]

[0112] As shown in Table 1, the positive electrode active material of Example 1 according to the present invention was found to have a single particle of lithium transition metal oxide consisting of primary particles with an average particle size of 2.0 μm and a primary particle of metal oxide with an average particle size of 0.2 μm located on the surface of the single particle. Thus, it can be seen that the positive electrode active material of the present invention has a different particle size between the primary particle forming the core and the primary particle located on the surface.

[0113] On the other hand, the positive electrode active materials of Comparative Examples 1 and 2 did not contain metal oxide primary particles, and therefore the corresponding average particle size could not be measured.

[0114] Experimental example 3: Evaluation of resistance characteristics Lithium secondary batteries were manufactured using the positive electrode active materials of Example 1 and Comparative Examples 1 and 2, and the resistance characteristics of each were evaluated.

[0115] Specifically, the positive electrode active materials prepared in the examples and comparative examples, the carbon black conductive material, and the polyvinylidene fluoride (PVdF) binder were mixed in a weight ratio of 96.5:1.5:2 in N-methylpyrrolidone (NMP) solvent to prepare a positive electrode slurry. The positive electrode slurry was applied to one side of an aluminum current collector, dried at 100°C, and then rolled to prepare a positive electrode.

[0116] On the other hand, lithium metal was used as the negative electrode.

[0117] An electrode assembly was prepared by interposing a porous polyethylene separator between the positive and negative electrodes, and the electrode assembly was placed inside a battery case, and an electrolyte was injected into the case to prepare a lithium secondary battery. The electrolyte was prepared by dissolving 1.0 M lithium hexafluorophosphate (LiPF6) in an organic solvent containing ethylene carbonate:ethyl methyl carbonate:diethyl carbonate (EC:EMC:DEC) in a volume ratio of 3:4:3.

[0118] Next, the lithium secondary battery was charged at a constant current of 0.4C at a low temperature (-10°C) to SOC5, SOC50 or SOC95, and then discharged at a constant current of 0.4C for 1,350 seconds to measure the voltage drop over the 1,350 seconds. This was then divided by the current value to measure the resistance at low temperature, which is shown in the table below.

[0119] [Table 2]

[0120] As shown in the results of Table 2 above, it was confirmed that the secondary batteries of the examples had improved low-temperature resistance compared to the comparative examples.

[0121] Experimental Example 4: Evaluation of capacity and resistance characteristics by charge / discharge cycle Each of the lithium secondary batteries prepared above was charged at room temperature at a constant current of 0.2 C to 4.25 V with a 0.05 C cut off. Then, it was discharged at a constant current of 0.2 C to 2.5 V. The above charge and discharge behavior was counted as one cycle, and from the second time onwards, charging at a constant current of 0.5 C to 4.25 V with a 0.05 C cut off and discharging at a constant current of 0.5 C to 2.5 V was counted as one cycle.

[0122] After repeating such a cycle 30 times, the capacity retention rate and the resistance increase rate of the secondary battery due to the cycle were measured and are shown in Table 3 below.

[0123] [Table 3]

[0124] As shown in the results of Table 3 above, it was confirmed that the secondary batteries of the examples had improved capacity retention rates, lower resistance change rates, and improved life characteristics compared to the comparative examples.

Claims

1. A lithium transition metal oxide containing 60 mol % or more of nickel relative to the total number of moles of transition metals other than lithium, and a coating layer containing a metal oxide located on a surface of the lithium transition metal oxide, The lithium transition metal oxide has an average particle size (D 50 ) is a single particle including a primary particle having a diameter of 0.7 to 3 μm, The metal oxide has an average particle size (D 50 ) is 0.5 μm or less, and the positive electrode active material contains one or more metal elements selected from the group consisting of Ni, Co, Mn, Al, B, Ti, Ta, W, and Nb.

2. The positive electrode active material according to claim 1, wherein the coating layer has a thickness of 0.02 to 2.4 μm.

3. 2. The positive electrode active material according to claim 1, wherein a volume ratio of the lithium transition metal oxide and the coating layer is 50:50 to 95:

5.

4. The lithium transition metal oxide has an average particle size (D 50 2. The positive electrode active material according to claim 1, wherein the particle diameter is 1 to 10 μm.

5. 2. The positive electrode active material according to claim 1, wherein one of the single particles is composed of 2 to 30 primary particles.

6. The positive electrode active material according to claim 1 , wherein the lithium transition metal oxide is represented by the following formula 1: [Chemical formula 1] Li 1+a Ni x Co y Mn z M 1 w O 2 In the above Chemical Formula 1, M 1 is at least one selected from the group consisting of Al, Mg, V, Ti and Zr, 0≦a≦0.5, 0.6≦x<1, 0<y≦0.4, 0<z≦0.4, 0<w≦0.04, and x+y+z+w=1.

7. (S1) preparing a transition metal hydroxide containing 60 mol % or more of nickel based on the total number of moles of the transition metal; (S2) mixing the transition metal hydroxide with a lithium source material and calcining the mixture at a temperature of 800 to 890° C. to prepare a single particle lithium transition metal oxide; (S3) heat-treating the lithium transition metal oxide at a temperature 30 to 50° C. higher than the firing temperature; (S4) mixing the heat-treated lithium transition metal oxide with a coating raw material containing one or more metal elements selected from the group consisting of Ni, Co, Mn, Al, B, Ti, Ta, W, and Nb, and heat-treating the mixture.

8. The method for producing a positive electrode active material according to claim 7, wherein in the step (S4), the heat treatment is carried out at a temperature of 600 to 700°C.

9. The method for producing a positive electrode active material according to claim 7 , wherein the calcination is carried out in an oxygen or air atmosphere.

10. A positive electrode for a lithium secondary battery, comprising the positive electrode active material according to claim 1 .

11. A lithium secondary battery comprising the positive electrode for lithium secondary batteries according to claim 10.

Citation Information

Patent Citations

  • Composite positive electrode active material, positive electrode containing the same, lithium battery and manufacturing method thereof

    JP2020068210A

  • Positive electrode active material for lithium secondary battery, method for producing the same, positive electrode for lithium secondary battery containing the same, and lithium secondary battery

    JP2020525993A

  • Positive electrode active material for secondary battery, method for producing the same, and lithium secondary battery including the same

    JP2021508161A

  • Cathode materials for rechargeable lithium-ion batteries

    JP2021508410A

  • composit cathode active material, cathode and lithium battery containing the material, and preparation method thereof

    KR1020140093529A